2020
DOI: 10.1021/acscatal.0c03036
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Nitrogen-Doped Intermetallic PtNi Catalyst for the Oxygen Reduction Reaction

Abstract: PtM (M = transition metals) nanomaterials have been recognized as promising catalysts for the oxygen reduction reaction (ORR) in fuel cells, with a much higher performance than pure Pt. However, the insufficient durability issue of PtM is often raised because of the fast dissolution of M in acid, impeding their commercialization. Herein, we report on a Ketjenblack (KB)-supported, nitrogen (N)-doped intermetallic PtNiN (Int-PtNiN/KB) catalyst that exhibits remarkably enhanced ORR activity and stability in an ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
115
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(121 citation statements)
references
References 55 publications
3
115
0
Order By: Relevance
“…PtPd and PtRu catalysts with different shapes and structure have been proved to be effective catalysts for MOR, because Pd and Ru can change the electronic structure of Pt [ 15 , 39 , 155 , 156 ]. In addition, PdPt nanocrystals also exhibited facet and composition-dependent catalytic activity for MOR.…”
Section: Applications Of Bimetallic Nanocrystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…PtPd and PtRu catalysts with different shapes and structure have been proved to be effective catalysts for MOR, because Pd and Ru can change the electronic structure of Pt [ 15 , 39 , 155 , 156 ]. In addition, PdPt nanocrystals also exhibited facet and composition-dependent catalytic activity for MOR.…”
Section: Applications Of Bimetallic Nanocrystalsmentioning
confidence: 99%
“…Many works in the literature have proved that PtNi catalyst exhibited much higher catalytic performance than pure Pt for the oxygen reduction reaction (ORR) in fuel cells. For example, Zhao and co-workers reported that intermetallic PtNi catalyst exhibited remarkably enhanced ORR activity in comparison to the disordered PtNi and commercial Pt/C, and the durability also was improved by N doping [15]. Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al reported an N-doped intermetallic L1 0 -PtNi catalyst, where the N atoms are located at the interstitial site in the L1 0 -PtNi lattice (Figure 12a-d). [89] Through PXRD and in situ EXAFS analyses, it was demonstrated that the N atoms were located at the interstitial sites in the L1 0 -PtNi lattice, forming alternating atomic layers of a Ni 4 -N moiety and Pt along the c-axis ([001] direction). The intermetallic N-doped PtNi (Int-PtNiN/KB) catalyst exhibited a mass activity of 1.83 A mg Pt -1 at 0.9 V RHE and maintained 72.7% of its initial mass activity after 30 000 cycles of ADT (Figure 12e,f).…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…Reproduced with permission. [89] Copyright 2020, American Chemical Society. g-i) In situ S-doping in IrO x nanocage (ICS NC).…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
See 1 more Smart Citation